Co-occurrence of AIDS and acute promyelocytic leukemia: a case report and review of the literature - Cheng Ai; Jianqiao Shentu; Hening Xu; Yongming Xia; Shiwei Duan (Frontiers in Hematology)
Acute promyelocytic leukemia (APL) is a rare and aggressive subtype of acute myelogenous leukemia (AML), characterized by the PML-RARA fusion gene. When APL presents concurrently with acquired immunodeficiency syndrome (AIDS), it creates unique challenges in diagnosis and treatment due to the immunocompromised state of the patient. This case report describes a 46-year-old male patient with long-standing AIDS who developed APL. Initial treatment involved all-trans retinoic acid (ATRA) monotherapy due to the patient’s severe lung infection and liver dysfunction, followed by the addition of arsenic trioxide (ATO) once infection and liver function improved. The patient achieved complete remission (CR) after combined ATRA and ATO therapy, with successful molecular remission of the PML-RARA fusion gene. We discuss the complexity of managing APL in the context of HIV infection, including the challenges posed by infections, liver dysfunction, and the impact of chemotherapy on antiretroviral therapy (ART). This case highlights the need for immediate initiation of ATRA in APL patients, even before genetic confirmation, and the potential therapeutic role of ATO in both leukemia treatment and HIV reservoir management. Further studies are needed to optimize treatment protocols for patients with concurrent AIDS and APL, focusing on personalized approaches to maximize efficacy while minimizing complications.